STOP! THAT’S MY SPACE: A PICTURE BOOK-BASED SAFETY EDUCATION TOOL FOR EDUCATORS AND CAREGIVERS TO EMPOWER CHILDREN - Nur Hidayah, Safarudin; Grace Wong, Wang Yiing; Natasha, Rusdy Wong (2026)
This teaching and learning innovation introduces Stop! That’s My Space, a storytelling-based educational tool developed to help educators and caregivers teach children about personal boundaries, body respect, and consent in a developmentally appropriate and culturally sensitive manner. The tool centers around a large-format picture book that combines relatable storytelling through thoughtfully designed characters representing Malaysia’s diverse ethnic backgrounds, body types, abilities, and age groups. Each character is crafted to reflect inclusivity and foster a sense of belonging through familiar cultural and visual cues. The primary objectives of this teaching innovation are to: (1) provide educators and caregivers with a practical and engaging tool to introduce personal space and child safety concepts; (2) promote inclusivity, empathy, and respect for diversity through culturally relevant storytelling; and (3) encourage meaningful adultchild conversations around personal safety across diverse early childhood education settings.The methodology involves the use of this picture book alongside an instructor guidebook, which includes structured lesson plans, printable resources, and page-by-page facilitation notes. These materials are designed for use in both formal and informal learning environments, including those with limited digital access. Educators deliver the sessions using the materials provided and are invited to offer feedback through a structured questionnaire to assess clarity, usability, and effectiveness. Findings from the pilot stage indicate positive responses from educators and caregivers. Many observed that children demonstrated increased confidence in asserting their personal boundaries. Children were also able to identify trusted adults and exhibited a clearer understanding of when and how to seek help. Educators appreciated how the structured, developmentally appropriate materials supported them in facilitating sensitive discussions in a safe and accessible way. Improvements were also noted in children’s use of safety-related vocabulary, their emotional expression, and overall awareness of respectful personal interactions. In conclusion, this book offers a flexible, narrative-based approach to early childhood education that prioritizes child safety through storytelling. Its inclusive design, practical format, and relevance to multicultural Malaysian classrooms position it as a valuable teaching innovation for fostering safer, more empathetic, and informed learning communities.